Sharing of risks in Islamic finance - Ahmet Sekreter (IBSU Scientific Journal (IBSUSJ), 2011)
For most of the people the prohibition on interest is the well known part of Islamic finance. Indeed, the concept of Islamic finance was not being discussed enough till financial crisis, after crisis it started to be seen as an alternative financial system for conventional finance. Sharing the risks is the main concept of Islamic finance and one of the main differences between conventional and Islamic finance. Depositors/savers do not bear any risk in conventional finance however Islamic finance has another solution which is called PLS (profit-loss sharing). Risks and profits between the parties involved in any financial transaction are shared by both financial institutions and depositors/savers with a predecided ratio.
Keywords: G20; G21; 330; Islamic finance; conventional finance; profit-loss sharing system